1999
DOI: 10.1111/j.1467-842x.1999.tb01285.x
|View full text |Cite
|
Sign up to set email alerts
|

The timeliness of notification of clinically suspected cases of dengue imported into north Queensland

Abstract: Objective: Evaluate the timeliness of notifications by medical practitioners of clinically suspected dengue importations into north Queensland (NQ). Describe the features the disease and determine the likely duration of viraemia prior to implementating public health measures. Method: Since December 1994, the Tropical Public Health Unit (TPHU) has maintained a register of all imported cases of dengue into NQ. Only confirmed viraemic cases were included in the study. Timeliness of notifications was defined as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…However, even mandatory reporting is not sufficient; additional efforts are needed to improve and maintain a high level of quality reporting. All suspected cases must be reported to a central dengue unit in the health ministry as rapidly as possible and providers should be reminded that timely reporting can lead to effective response [26]. Laboratory confirmation of suspected cases should always be sought, except during outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…However, even mandatory reporting is not sufficient; additional efforts are needed to improve and maintain a high level of quality reporting. All suspected cases must be reported to a central dengue unit in the health ministry as rapidly as possible and providers should be reminded that timely reporting can lead to effective response [26]. Laboratory confirmation of suspected cases should always be sought, except during outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is often fragmented reporting, inadequate methods of notification, and weakness in the transfer of case information from local to central level for analysis, with a lack of local use of analysis data. This may lead to neglect of an immediate response, especially if a number of intermediaries are in place as has been identified [19]. It may be suggested that although a coordinated response from local government may be difficult in some settings, the use of local data for risk communication to the public, clear reporting flowcharts in place, a functional feedback system, data analysis also at the lowest possible level, and capacity building in surveillance at the periphery may be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…We also included areas of the US with dengue and covered by their national immunization program and Australia (North Queensland) and Taiwan where dengue epidemics occurred following introductions by travelers. 32,33 While dengue occurs in Africa, none of these countries were included because of the unknown public health impact. 34 We excluded dengue-endemic countries with a population of <100,000.…”
Section: Discussionmentioning
confidence: 99%